2011
DOI: 10.1590/s0004-28032011000200008
|View full text |Cite
|
Sign up to set email alerts
|

HBV and HCV serological markers in patients with the hepatosplenic form of mansonic schistosomiasis

Abstract: We observed a higher prevalence of serological markers for HBV and a lower prevalence of anti-HCV. Our results indicate that females and patients of an advanced age are the most affected categories and that patients that received multiple transfusions are at a higher probability of HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In this series, 33.5 % of HBsAg-positive patients had evidence of schistosomal infection. The proportion shown in our study is within what is expected for those areas endemic for both diseases [4][5][6][7][8][9]. We have found no differences with regard to the likelihood of fibrosis among patients co-infected and those who just had chronic hepatitis B.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In this series, 33.5 % of HBsAg-positive patients had evidence of schistosomal infection. The proportion shown in our study is within what is expected for those areas endemic for both diseases [4][5][6][7][8][9]. We have found no differences with regard to the likelihood of fibrosis among patients co-infected and those who just had chronic hepatitis B.…”
Section: Discussionsupporting
confidence: 72%
“…There are an estimated 250 million people affected by schistosomiasis in the world, with more than 90 % of the cases occurring in Sub-Saharan Africa [3]. The similar geographic distribution of these two diseases enables high co-infection prevalence in this area [4][5][6][7][8]. Published data on the prevalence of co-infection are scarce for Sub-Saharan countries, with just one study from Ethiopia reporting a co-infection rate of 50.3 % in patients with ultrasonographically demonstrated periportal fibrosis and any serological marker of HBV infection, and 16.1 % for those who were positive for HBsAg [9].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is found in 78 countries across Latin America, Africa, and Asia 1 . Brazil is the worst affected country in the Americas 2 , with 42.9 million people exposed to the risk of infection and approximately 6.8 million infected individuals [3][4][5] .…”
mentioning
confidence: 99%
“…Viral hepatitis is a serious public health problem, not only in Brazil but also in many other countries worldwide 7,8 . Despite the controversies in the literature about the prevalence of schistosomiasis and viral hepatitis coinfection, some reports have indicated that the presence of both infections accelerates and aggravates the process of fibrosis in the liver and can lead to the development of cirrhosis and hepatocellular carcinoma 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation